MRI of respiratory dynamics with 2D steady-state free-precession and 2D gradient echo sequences at 1.5 and 3 Tesla: an observer preference study. - Fabel M; Wintersperger BJ; Dietrich O; Eichinger M; Fink C; Puderbach M; Kauczor HU; Schoenberg SO; Biederer J; Fabel, M; Wintersperger, B J; Dietrich, O; et al. (European Radiology, 2009)
To compare the image quality of dynamic lung MRI with variations of steady-state free-precession (SSFP) and gradient echo (GRE) cine techniques at 1.5 T and 3 T. Ventilated porcine lungs with simulated lesions inside a chest phantom and four healthy human subjects were assessed with SSFP (TR/TE=2.9/1.22 ms; 3 ima/s) and GRE sequences (TR/TE=2.34/0.96 ms; 8 ima/s) as baseline at 1.5 and 3 T. Modified SSFPs were performed with nine to ten images/s (parallel imaging factors 2 and 3). Image quality for representative structures and artifacts was ranked by three observers independently. At 1.5 T, standard SSFP achieved the best image quality with superior spatial resolution and signal, but equal temporal resolution to GRE. SSFP with improved temporal resolution was ranked second best. Further acceleration (PI factor 3) was of no benefit, but increased artifacts. At 3 T, GRE outranged SSFP imaging with high lesion signal intensity, while artifacts on SSFP images increased visibly. At 1.5 T, a modified SSFP with moderate parallel imaging (PI factor 2) was considered the best compromise of temporal and spatial resolution. At 3 T, GRE sequences remain the best choice for dynamic lung MRI.